2016
DOI: 10.1097/mib.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraception Use is Common Among Patients with Inflammatory Bowel Diseases and an Elevated Risk of Deep Vein Thrombosis

Abstract: Background Persons with inflammatory bowel disease (IBD) have an increased risk of venous thromboembolism (VTE). We sought to examine whether self-report of hormonal contraception (HC), as a proxy for exposure to estrogen-based contraception, was less common for women with multiple risk factors for VTE. Methods We examined the prevalence of personal use of hormonal birth control in a large internet-based cohort of patients with IBD. To determine whether HC was less common among IBD patients with increased ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
4
1
Order By: Relevance
“…Because of insufficient research regarding HC and their effects on IBD-related outcomes, women living with IBD may choose to avoid HC all together. Though the prevalence of HC users in this study was low compared with other studies among patients with IBD which reported 33% and 43% using HC, 8,27 all proportions were lower than the average 65% of current HC users found among the general population. 18 Many studies have focussed on the risks of development of CD or UC 28,29 rather than the potential positive or negative effects of HC on patients living with IBD.…”
Section: Relationship Between Inflammation and Hccontrasting
confidence: 85%
See 1 more Smart Citation
“…Because of insufficient research regarding HC and their effects on IBD-related outcomes, women living with IBD may choose to avoid HC all together. Though the prevalence of HC users in this study was low compared with other studies among patients with IBD which reported 33% and 43% using HC, 8,27 all proportions were lower than the average 65% of current HC users found among the general population. 18 Many studies have focussed on the risks of development of CD or UC 28,29 rather than the potential positive or negative effects of HC on patients living with IBD.…”
Section: Relationship Between Inflammation and Hccontrasting
confidence: 85%
“…The longitudinal design allowed for regular tracking of disease activity over a year, with multiple sampling of validated measures. 17,36 However, the open-ended self report of contraceptive medication may have resulted in under-reporting of use, based on previous literature, 8,27,33 as some participants may not have considered birth control as a medication, and missed reporting it. Further, the focus of this study was to assess the effects of HC on IBD disease activity considering all forms of HC (oral, IUD, ring, patch, implant, injection).…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Cotton et al demonstrated that women with IBD do not carry an increased risk of VTE compared with healthy controls, even in the presence of concomitant thrombotic risk factors such as cigarette smoking or cancer. 101 Furthermore, a 2015 study did not find an increased thromboembolic risk in women with IBD receiving oral contraceptive therapy versus healthy women. 102 Nevertheless, the U.S. Medical Eligibility Criteria for Contraceptive Use recommends the use of alternative contraceptive methods in patients with IBD where possible and advise against their use altogether in patients with severe forms of IBD, with complications, undergoing surgery, or steroid treatment.…”
Section: Prevention Of Vte In Ibdmentioning
confidence: 98%
“…In CD patients, oral contraceptive drugs are well-known risk factors for TE[ 75 ]. In spite of this, Cotton et al [ 76 ] in a large internet-based cohort of patients with IBD found that use of hormonal contraceptives in women with multiple risk factors for TE was similar to that in women without risk factors. Thus, patients with IBD should be asked about risk factors for thromboembolic disease to have an opportunity for alternative contraception.…”
Section: Risk Factors Of Thromboembolic Complications In Ibdmentioning
confidence: 99%